Proteomics in drug discovery - Noberini, Roberta (Henry Stewart Talks, 2025)
Mass spectrometry-based proteomics, Applications of proteomics at different stages of drug discovery, Target identification / deconvolution, Post translational modification profiling (Histone profiling), Chemical proteomics, Activity-based probe profiling (ABPP), Thermal proteome profiling, Cellular Thermal Shift Assay (CETSA)